Quality of Transfusion Products in Blood Banking - Franchini, Massimo; Capuzzo, Enrico; Turdo, Rosalia; Glingani, Claudia (Seminars in Thrombosis and Hemostasis, 2014)
The primary goal in transfusion medicine and cellular therapies is to promote high standards of quality and produce ever safer and more efficacious products. The establishment of a transfusion service quality management system, which includes several organizational structures, responsibilities, policies, processes, procedures, and resources, is now mandatory and widely regulated worldwide. In this review, we summarize the current knowledge on the quality system in transfusion medicine as applied to the production of blood components, including red blood cells, platelets, and fresh frozen plasma.
Keywords: blood components; fresh frozen plasma; red blood cells; platelet concentrates; quality controls